1996
DOI: 10.1002/(sici)1097-0029(19960301)33:4<320::aid-jemt3>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the human cornea

Abstract: The transparent nature of the cornea and its importance in the visual pathway as the major refracting lens of the eye have intrigued workers in many different disciplines and their studies have added immeasurably to the understanding of the cornea in health and disease. Reviews of the structure of the cornea date back to the earliest days of electron microscopy (Hogan et al., 1971; Klyce and Beuerman, 1988; Kuwabara, 1978; Rouiller et al., 1954), yet, due to changing insights into corneal structure provided by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
50
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(63 citation statements)
references
References 30 publications
13
50
0
Order By: Relevance
“…The lamina fibroreticularis lies beneath the lamina densa, contains anchoring fibrils comprising type VII collagen, and forms a complex network with type I and type V collagens to attach the epithelium and its basement membrane to the underlying Bowman layer (Figure 1). [15][16][17] Although the clinical outcomes of epi-LASIK have been evaluated, [18][19][20] the exact site of epithelial separation during epi-LASIK remains unclear. Pallikaris et al 12 found that the epithelial separation was beneath the basement membrane with intact basal cells.…”
supporting
confidence: 86%
“…The lamina fibroreticularis lies beneath the lamina densa, contains anchoring fibrils comprising type VII collagen, and forms a complex network with type I and type V collagens to attach the epithelium and its basement membrane to the underlying Bowman layer (Figure 1). [15][16][17] Although the clinical outcomes of epi-LASIK have been evaluated, [18][19][20] the exact site of epithelial separation during epi-LASIK remains unclear. Pallikaris et al 12 found that the epithelial separation was beneath the basement membrane with intact basal cells.…”
supporting
confidence: 86%
“…In some mammals, there is a mitotic turnover of endothelial cells and a mitotic response to endothelial injury. 2 However, in both human and non-human primates, although mitosis occurs in the young, 32 the endothelial cell population does not regenerate in any significant fashion in the adult. 2,32 This gives rise to a decreasing cell density with age.…”
Section: Corneal Endothelium In Vertebrates Collin and Collinmentioning
confidence: 99%
“…Warm fixative consisting of 2% glutaraldehyde and 1% paraformaldehyde in 0.1 M sodimn cacodylate (NaC) buffer (pH 7.4) containing 0.02% picric acid was slowly introduced into the plate and left for 2 h (Beuerman and Pedroza, 1996). The plates were washed with 0.1 M NaC buffer and the cells were scraped off the plate, pelleted, briefly resuspended, and transferred to a 1.5-ml nficrocentrifuge tube.…”
Section: In Vivo Transfection Of Rabbit Lacrimal Gland a Normal Malementioning
confidence: 99%